PERAN PRODUKTIF ISTRI BURUH NELAYAN DALAM MEMENUHI KEBUTUHAN KELUARGA DI DESA JATIREJO KECAMATAN LEKOK KABUPATEN PASURUAN (STUDI KASUS PADA UNIT USAHA PENGERINGAN IKAN) - Kodriyah, Lailatul; Suharso, Pudjo; Mardiyana, Lisana Oktavisanti (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2024)
This research aims to describe the productive role of fishermen's wives in meeting family needs in Jatirejo Village, Lekok District, Pasuruan Regency in the fish drying business unit. This type of research is descriptive qualitative. Data collection uses interview methods, observation methods, and document methods. The subject of this research is the wife of a fishing worker in Jatirejo Village. The results of this research show that the wives of fishing workers play a productive role in the fisheries business unit by working as splitters and dryers of fish based on economic conditions, their own will and the support of their husbands. The productive role of fishermen's wives contributes to fulfilling the family's daily needs because the wages they receive become a source of financing their needs, especially in fulfilling their children's education. Meanwhile, most of the food needs are met from the husband's income. For other types of needs, such as clothing, shelter and health, these are fulfilled at certain times.